Existence of positive solutions to a discrete fractional boundary value problem and corresponding Lyapunov-type inequalities - Chidouh, Amar (2018)
We prove existence of positive solutions to a boundary value problem depending on discrete fractional operators. Then, corresponding discrete fractional Lyapunov-type inequalities are obtained.